Effectt of curry leaves (murraya sp.) and peppermint (mentha sp.) plate on shelf life irradiated chicken tikka - Ahire Girish sureshrao (Department of Livestock Products Technology, College of Veterinary and Animal Sciences, 2009)
To study the beneficial effects of irradiation, application of curry leaves (Murraya sp.) and peppermint (Mentha sp.) paste in the marinade of chicken tikka, the present study was conducted at Department of Livestock Products Technology, College of Veterinary and Animal Sciences, Mannuthy. Chicken tikka was prepared incorporating zero per cent, 1.0% CL, 1.0% PL or both and it was fried separately. After cooling, tikka was packed in HDPE (50µ) packets. Half of the packets in each treatment group were subjected to irradiation at 2.5 kGy using Gamma Chamber 5000 and stored at chiller temperature (1–40C). The irradiated and non-irradiated chicken tikka of various treatment groups under chiller storage were analysed for different quality parameters viz., physical, physicochemical, microbiological analysis and organoleptic evaluation on the day of preparation and on days 5, 10, 15, 20, 25, 30, 45 and 60 or until spoilage whichever was earlier. The samples were subjected to proximate analysis on the day of preparation. Shelf life of chicken tikka was assessed based on the physical signs of spoilage. The non-irradiated control samples had a shelf life of 27-30 days in chiller storage. Application of CL, PL and both had extended the shelf life of the product by 3-4 days, 7-8 days and nearly 5 days respectively. Irradiated samples had approximately two times shelf life than that of non-irradiated samples in all treatment groups under chiller storage. The C-IR and PL-IR samples had storage life of 61-63 days and 68-70 days respectively in chiller storage. Irradiation did not significantly affect any of the proximate composition. Moisture, fat and protein were significantly affected by application of CL, PL and their combination. The highest energy content of 255.40±2.79 kcal/100g was recorded in PL-IR group. The pH of chicken tikka samples did not show any significant difference due to irradiation in different treatment groups on the day of preparation. As storage period enhanced pH had significantly (P<0.05) reduced in all treatment groups except in CL-NR and CL-IR groups where, pH had significantly (P<0.05) increased. The TBARS values were non significantly increased due to irradiation on the day of preparation in various treatment groups. Addition of CL, PL and CLPL alone in the marinade had a beneficial effect in reducing the TBARS compared to control samples in both NR and IR groups. TV showed decreasing trend due to irradiation as well as application of CL, PL and CLPL. Storage had significant (P<0.05) effect in increasing both these physicochemical properties. Aerobic plate count, Psychrotrophic count and yeast and mould count were significantly (P<0.05) reduced due to irradiation and combination of irradiation with CL, PL and CLPL. Whereas, extend of reduction due to application of CL, CLPL alone was not up to the level of PL alone to non-irradiated groups. PL-IR samples had recorded the lowest counts among all treatment groups throughout the storage period. As storage period enhanced the counts were significantly (P<0.05) increased. The organoleptic qualities were assessed with help of nine point Hedonic scale. The colour, juiciness, tenderness and overall acceptability of the product were improved by irradiation as well as addition of CL, PL and CLPL. A gradual decrease in organoleptic qualities was observed only after 5th day of storage in most of the samples. Even on 60th day of chiller storage, the samples had an overall acceptability score of above 7 indicating the samples are preferred by the consumers. The cost of production was Rs. 122.30, Rs. 123.30, Rs. 125.30 and Rs. 126.30 per kg for the control, CL, PL and CLPL treatment groups respectively. Irradiation of ready-to-eat chicken tikka was beneficial for enhancing the keeping quality of the product under chilling condition without affecting qualities. Addition of herbal pastes containing natural antioxidants in the marinade for the preparation of chicken tikka was found to be beneficial in reducing many of undesirable effects. Among the herbal pastes viz., peppermint paste, curry leaf paste and their combination, it was found that peppermint paste had better effect than the other two. The microbial counts were significantly (P<0.05) reduced due to irradiation at 2.5 kGy, the lowest limit prescribed by PFA. Considering extended shelf life, wholesomeness of the product, reducing the microbial load and energy saving aspects, preparation of chicken tikka incorporating peppermint paste in the marinade and followed by irradiation can be advocated as a suitable method for preparation of ready-to-eat value added meat products.